(untitled) (Current Horticulture, 2024)
Experiments were conducted to study the combining ability for yield attributing traits in CMS based hybrids of chilli (Capscum annuum L.) at Vasantrao Naik Marathvada Krishi Vidyapeeth, Parbhani, Maharashtra, India. Sixteen parents and 60 F1 s produced in line × tester mating design were used. The variance due to g,c,a and s,c,a were significant for all characters. The fruit diameter of s,c,a variance were non - significant. The parents, BSPRL-171, BSPRL-066, BSPRL-188, Phule Jyoti, Pusa Sadabahar, PBNC-1, and Parbhani Tejas, were good general combiner for fruit and yield. Hybrids, BSPRL-066 × Phule Jyoti, BSPRL-171 × Phule Jyoti, BSPRL-171 × Bydagi, BSPRL-171 × G-4, BSPRL-226 × Kokan Kirti and BSPRL-189 × Bydagi had good s,c,a effects for fruit and yield.